THE PORTRAYAL OF DISCRIMINATION TOWARDS FEMALE CHARACTERS IN THE HIDDEN FIGURES MOVIE - Eliyana, Rika; Ariani, Setya; Lubis, Indah Sari (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This research discussed the issues of discrimination occurred toward the black female characters in The Hidden Figures movie. It aimed to describe the types of discrimination and to explain the impacts toward the black female characters. The researcher used the qualitative research as the method and feminist literary criticism as the approach of this research. The data derived from narrations and dialogues in the movie script related to the research questions. The findings of this research showed that there were two types of discrimination portrayed in the movie; those are derogation and denial. The findings also showed that the impacts of discrimination toward black female characters emerged in psychological and economic fields.